PENGARUH RASIO KEUANGAN TERHADAP KONDISI FINANCIAL DISTRESS BANK UMUM SYARIAH DI INDONESIA - SUHADI, ARINNA; KUSUMANINGTIAS, ROHMAWATI (Jurnal Akuntansi AKUNESA, 2018)
This research aims to assess the condition of the Financial Distress of public Islamic bank in Indonesia. The samples on this research 11 public Islamic bank whohave met the criteria of research and publish the annual financial report of the 2013-2017 period. Technique of data analysis in this study uses the SPSS (Statistical Product and Service Solutions), and there are varibel dependent Financial Distress as well as independent variable NPF (Net Performing Finance), STM (Short Term Mismatch), GCG (Good Corporate Governance), ROA (Return On Assets), and CAR (Capital Adequacy Ratio). The results of this research show that on variable STM and CAR has an posittive effect on the Financial Distress of public Islamic bank in Indonesia, and variable GCG has an negative effect on the Financial Distress of public Islamic bank in Indonesia. Whereas in NPF and ROA variable has no effect on the Financial Distress of public Islamic bank in Indonesia. Keywords:Financial Distress, NPF (Net Performing Finance), STM (Short Term Mismatch), GCG (Good Corporate Governance), ROA (Return On Assets), and CAR (Capital Adequacy Ratio).